MORFOMETRIA DA ASA E DO EDEAGO DE DUAS ESPÉCIES DE Drosophila ENDÊMICAS DA AMÉRICA DO SUL - Trava, Bruna Memari (2014)
Drosophila maculifrons belongs to the guaramunu group and in habits forests in Brazil. It can be found mainly in the Atlantic Forest domains of the south, southeast and central-west regions. On the other hand, D. ornatifrons belongs to the guarani group and has been collected all over Brazil, but in small number sample. In spite of the great amount of cytogenetics and molecular data for these species (mainly related to phylogenetic analyses), there is no comparative study using morphological characters in natural populations. Thus, in order to quantify and identify some patterns of morphological variation in populations of these species, this work aimed to analyze the aedeagus and wing morphology in seven populations of D. maculifrons and four populations of D. ornatifrons using geometric morphometry of samples collected in areas of ombrophylous mixed forest and semideciduous seasonal forest. Our results showed that there was statistically significant variation for wing size and shape among the populations for both species. Drosophila ornatifrons populations had greater Procrustes distance among each other than the distances among D. maculifrons populations. This variation in the wing morphology detected among populations of both species could be related to their ecological features. It is possible that D. ornatifrons have a narrower ecological specificity, which hinder its occurrence and capture, and D. maculifrons is probably more generalist and, therefore, suffer less environmental pressure when compared to D. ornatifrons. Regarding the aedeagus, there was no morphological differentiation for shape in D. ornatifrons, while in D. maculifrons it was detected statistically significant differences among sampled populations, mainly between those located in the south against those from the southeast regions of Brazil. The differences detected for these two morphological markers in the patterns of variation corroborated that the differentiation in the genital characters is not always followed by similar differentiation in the morphology of the rest of the body. Despite wing and aedeagus of D. maculifrons and D. ornatifrons have depicted different results in the populational analyses, the evolution and morphological divergence among populations of these species seems to be linked to differential niche exploitation and/or to differences in the temperature in the sampled localities